2006
DOI: 10.4321/s0365-66912006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Diplopía postcirugía de catarata con anestesia subtenoniana

Abstract: Purpose: To study the clinical signs, treatment and prognosis of strabismus after sub-Tenon's anesthesia for cataract surgery. Methods: Eight patients without previous strabismus developed incommitant diplopia immediately after cataract surgery; the left eye was affected in five patients and the right eye in three. Restrictive strabismus was diagnosed with the cover test, prisms, and active and passive ductions in all cases. In seven cases the deviation was vertical and in one patient it was horizontal. The av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…The sub-Tenon anesthesia used in cataract surgery is responsible for diplopia and restrictive strabismus secondary to muscle contracture, fibrosis, and palsy. Botulinum toxin is effective in only 25% of cases of muscle palsy, before development of muscular fibrosis, which is frequent and has an early onset in older patients 7 . In our study, outcome was successful in 40% (2/5) of cases secondary to retinal surgery, in which botulinum toxin was injected early (1–4 months after onset of symptoms).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…The sub-Tenon anesthesia used in cataract surgery is responsible for diplopia and restrictive strabismus secondary to muscle contracture, fibrosis, and palsy. Botulinum toxin is effective in only 25% of cases of muscle palsy, before development of muscular fibrosis, which is frequent and has an early onset in older patients 7 . In our study, outcome was successful in 40% (2/5) of cases secondary to retinal surgery, in which botulinum toxin was injected early (1–4 months after onset of symptoms).…”
Section: Discussionsupporting
confidence: 45%
“…The effect of botulinum toxin is independent of the initial deviation 6 . Other types of restrictive strabismus secondary to retinal detachment surgery, cataract surgery, and strabismus surgery have been treated with botulinum toxin, with variable results 7, 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a small number of isolated cases of long standing strabismus, usually involving the inferior rectus. Splerer and Schwalb have reported a superior oblique palsy that resolved after one month,40 while Merino et al reported eight cases of extraocular muscle dysfunction lasting more than 6 months, four of which required strabismus surgery 41. It is to be noted that all cases received an STB using 5% lignocaine, which is concentrated enough to cause direct myotoxicity.…”
Section: Complications Of Sub-tenon’s Anesthesiamentioning
confidence: 98%
“…Sometimes orthoptic exercises help, for example, in convergence insufficiency or temporary disruption of fusion. The other less invasive procedures are injections with botulin toxin into hyperactive muscle [ 22 ]. Surgical treatment of postcataract diplopia is applied as the second choice, when the deviation is stable.…”
Section: Treatmentmentioning
confidence: 99%